Antisense oligonucleotide targeting CD39 improves anti-tumor T cell immunity. Issue 1 (12th March 2019) - Kashyap, Abhishek S.; Thelemann, Tamara; Klar, Richard; Kallert, Sandra M.; Festag, Julia; Buchi, Melanie; Hinterwimmer, Lisa; Schell, Monika; Michel, Sven; Jaschinski, Frank; Zippelius, Alfred
Abstract : Background: Cancer cells are known to develop mechanisms to circumvent effective anti-tumor immunity. The two ectonucleotidases CD39 and CD73 are promising drug targets, as they act in concert to convert extracellular immune-stimulating ATP to adenosine. CD39 is expressed by different immune cell populations as well as cancer cells of different tumor types and supports the tumor in escaping immune recognition and destruction. Thus, increasing extracellular ATP and simultaneously reducing adenosine concentrations in the tumor can lead to effective anti-tumor immunity. Methods: We designed locked nucleic acid (LNA)-modified antisense oligonucleotides (ASOs) with specificity for human or mouse CD39 that do not need a transfection reagent or delivery system for efficient target knockdown. Knockdown efficacy of ASOs on mRNA and protein level was investigated in cancer cell lines and in primary human T cells. The effect of CD39 knockdown on ATP-degrading activity was evaluated by measuring levels of ATP in tumor cell supernatants and analysis of T cell proliferation in the presence of extracellular ATP. The in vivo effects of CD39-specific ASOs on target expression, anti-tumor immune responses and on tumor growth were analyzed in syngeneic mouse tumor models using multi-color flow cytometry. Results: CD39-specific ASOs suppressed expression of CD39 mRNA and protein in different murine and human cancer cell lines and in primary human T cells. Degradation of extracellular ATP was strongly reduced by CD39-specific ASOs. Strikingly, CD39 knockdown by ASOs was associated with improved CD8 + T cell proliferation. Treatment of tumor-bearing mice with CD39-specific ASOs led to dose-dependent reduction of CD39-protein expression in regulatory T cells (Tregs) and tumor-associated macrophages. Moreover, frequency of intratumoral Tregs was substantially reduced in CD39 ASO-treated mice. As a consequence, the ratio of CD8 + T cells to Tregs in tumors was improved, while PD-1 expression was induced in CD39 ASO-treated intratumoral CD8 + T cells. Consequently, CD39 ASO treatment demonstrated potent reduction in tumor growth in combination with anti-PD-1 treatment. Conclusion: Targeting of CD39 by ASOs represents a promising state-of-the art therapeutic approach to improve immune responses against tumors.